Crosswind aerodynamics of sports utility vehicles - Chadwick, Andrew (Cranfield University, 1999)
Crosswind gusts have a continuous influence on the ride and handling of road vehicles. At low speeds the effect is negligible but as both car and wind speeds increase there is a reduction in refinement, ride quality is degraded and it becomes tiring to drive. Future environmental legislation concerning the reduction of carbon dioxide emissions will lead to a lighter road vehicle and a corresponding increase in crosswind sensitivity. The aerodynamicist's approach to understanding the fluid flow around a vehicle when subjected to a crosswind has conventionally been through steady state model tests where aerodynamic force and moment data are taken for different yaw angles. The accuracy of this data has previously been questioned because of a lack of simulation of the transient nature of the crosswind gust. Additionally, although force and moment data can tell the aerodynamicist which are the principle loads influencing a vehicles response in a crosswind, they fail to identify the specific regions on the vehicle that contribute to these aerodynamic loads. This can only be achieved by pressure mapping the model surface and although such a technique has been employed during steady state tests, no research has been presented with the correct modeling of the transient crosswind gust. To gain an initial understanding of the complex time dependent and separated flow fields around bluff vehicles, such as sports utility vehicles, when subjected to a crosswind, aerodynamic force, moment and surface pressure data of simple geometric shapes has been collected on the Cranfield crosswind track facility. Steady state data has been obtained from conventional wind tunnel tests and compared with the transient data. Unique pressure animations identify the growth and collapse of vortices on the leeward face as the primary transient characteristic and which produce peak aerodynamic yawing moments up to double that seen in the steady state.